Optimization of Green Open Space in Urban Areas Based on Local Wisdom in Medan City - Mohammad Yusri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Local Wisdom is a local efficient legacy to green movement, but The Green City concept is complicated regulations in Indonesia. The goverment has contributed to the priority its program. On stipulated regulation the Minister of Home Affairs Instruction number 14 on 1998 that Green Open Space (RTH) is spaces within the city or wider area both in the form of elongated areas / lanes which more open in nature with basically no buildings which functions as urban parks, urban forests, urban recreation, sports activities, cemeteries, agriculture, green lanes and green yards. There are several problems in realizing urban areas using Green City parameters. Among these problems are an increase in the population in urban areas (urbanization), a decline in the quality of the urban environment that brings various consequences of problems in the city of Medan, including increased urban poverty, traffic congestion, rising sea levels, meeting uneven infrastructure needs, increasingly many slums, and floods. The purpose of this study is to find out how the Urban Environment and its Implementation are in accordance with the parameters of Green Cities (Green Open Space, Green Waste, Green Transportation, Green Water, Green Energy, Green Building, Resilience City), to find out how the principles of Green Cities, and to find out how the policies are in implementing the Green City principles. The method used in this research is descriptive-explorative-qualitative research combined with comparative methods, descriptive-explorative research is carried out by survey and library research methods while the qualitative method is carried out with a case study method that aims to explain the application of Green City parameters in environmental design the cities studied, and the comparative method used to explain the condition of the built urban environment in accordance with the Medan City Medium-Term Development Plan (RPJMD) for 2016-2020 with Green City parameters.